Sistem Informasi Administrasi Dan Keuangan GMIT Ebenhaezer Larantuka Berbasis Web Guna Mempermudah Laporan Keuangan - Sakaria, Setiabudi; Triwibowo, Eriech Ragil; Cahyadiana, Windarini (LPPM STIKI MALANG, 2021)
In today's digital era, the development of people's lives is increasingly broad and unlimited with the presence of the internet, including the GMIT Ebenhaezer Church in Larantuka which currently still uses the manual method in carrying out its financial administration. Problems that occur today include difficulties in data processing, and the process of calculating the income and expenditure of Church cash and reports for assemblies and Servants of God. In research and making administrative applications made with PHP and MYSQL, it is intended to overcome the problems that occur at this time, namely processing administrative data, calculating cash income and expenditure and financial reports needed by the Assembly and Pastor for decision making to facilitate the making of church financial reports so that transparent in financial management as well as accountability to church members who have provided funds to this church